Socio-Economic Functions Across Sustainable Farming Systems - Maharjan, Keshav Lall (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to present research on Socio-Economic Functions Across Sustainable Farming Systems, specifically on environmental conservation agriculture/climate-smart agriculture, which boosts nature-positive production, raises the welfare of producers; agricultural biotechnology, which contributes to economic and environmental sustainability; community-based extension and marketing of farm produce, which ensures the livelihood of producers and access to safe and nutritious food; and building a society resilient to all kinds of crises and hazards/disasters.This reprint reveals: 1) Drivers and dynamics of environmental conservation agriculture, the sustainable farming systems in Japan to address climate change, biodiversity conservation, sustainable production, welfare of producers and leveraging their participation in Globally Important Agricultural Heritage Systems. 2) Biotech crops in the Philippines can coexist with the practice of climate resilient environmental conservation agriculture. 3) Community-based extension services, such as farmer field school, disaster management practices, such as flood adaptation strategy, and marketing strategy of farm products enhance the welfare of rural population in Bangladesh.4) Identification of socio-economic characteristics associated with farming practices, food safety, food security and their constraints in South Africa and Senegal. 5) Benefit of financing agricultural cooperatives to enhance sustainable production in Romania.